Comparison of doublet and triplet therapies for metastatic hormone-sensitive prostate cancer: A systematic review and network meta-analysis - Wang, Lei; Li, Chunxing; Zhao, Zichen; Li, Xiaojian; Tang, Chong; Guan, Zhenpeng; Sun, Feng; Gu, Jin; Li, Ningchen (Frontiers in Oncology, 2023)
Background The best choice of first-line treatment for metastatic hormone-sensitive prostate cancer (mHSPC) is unclear. We aimed to compare the effectiveness and safety determined in randomized clinical trials of doublet and triplet treatments for mHSPC. Methods Medline, Embase, Cochrane Central and ClinicalTrials.gov were searched from inception through July 01, 2022. Eligible studies were phase III randomized clinical trials evaluating androgen deprivation treatment (ADT) alone, doublet therapies [ADT combined with docetaxel (DOC), novel hormonal agents (NHAs), or radiotherapy (RT)], or triplet therapies (NHA+DOC+ADT) as first-line treatments for mHSPC. Outcomes of interest included overall survival (OS), progression-free survival (PFS) and grades 3-5 adverse events (AEs). Subgroup analyses were performed based on tumor burden. The effects of competing treatments were assessed by Bayesian network meta-analysis using R software. Results Ten trials with 12,298 patients comparing nine treatments were included. Darolutamide (DARO) +DOC+ADT ranked best in terms of OS benefits (OR 0·52 [95% CI 0·39–0·70]), but its advantages were all statistically insignificant compared with other therapy options except for DOC+ADT (OR 0·68 [95% CI 0·53–0·88]) and RT+ADT (OR 0·57 [95% CI 0·40–0·80]). In terms of PFS, enzalutamide(ENZA)+DOC+ADT (OR 0·32 [95% CI 0·24–0·44]) and abiraterone and prednisone (AAP) +DOC+ADT (OR 0·33 [95% CI 0·25–0·45]) ranked best. For patients with high volume disease (HVD), low volume disease (LVD), and visceral metastases, the optimal therapies were AAP+DOC+ADT (OR 0·52 [95% CI 0·33–0·83]), apalutamide+ADT (OR 0·52 [95% CI 0·26–1·05]) and DARO+DOC+ADT (OR 0·42 [95% CI 0·13–1·34]), respectively. For safety, AAP+DOC+ADT (OR 3·56 [95% CI 1·51–8·43]) ranked worst with the highest risk of grade 3−5 AEs. Conclusions Triple therapies may further improve OS and PFS but may be associated with a decrease in safety. Triplet therapies could be suggested for HVD patients, while doublet combinations should still be preferred for LVD patients. Systematic Review Registration https://www.crd.york.ac.uk/PROSPEROFILES/303117_STRATEGY_20220202.pdf, identifier CRD4202303117.